The Role of Family Socialization Function on The Prevention of Violence in Interpersonal Relationship (Dating) in High School Student in South Sulawesi - Torro, Supriadi; Darmayanti, Dyan Paramitha; Kasmita, Maya; R, Nurazizah Rahmi (Seminar Nasional LP2M UNM, 2024)
Abstrak. This study aims to determine the effect of socialization function on the prevention of violence in interpersonal relationships (dating) in high school students in South Sulawesi. The research method used was a quantitative approach by collecting data through questionnaires from 208 respondents of high school students in South Sulawesi. Data analysis was conducted using simple linear regression test, t test, and coefficient of determination test. The results showed that the socialization function had a significant effect on the prevention of violence in interpersonal relationships (dating) in high school students in South Sulawesi. The coefficient of determination shows that the socialization function contributes to variations in violence prevention. This study provides important implications for stakeholders to develop strategies that involve socialization in an effort to prevent violence in interpersonal relationships among high school students. Keywords: Dating Violence, Socialization Function, Violence Prevention, High School Students